Eradication of superficial fungal infections by conventional and novel approaches: a comprehensive review. (February 2014) - Kumar, Lalit; Verma, Shivani; Bhardwaj, Ankur; Vaidya, Shubha; Vaidya, Bhuvaneshwar
Abstract During the last two decades, the occurrence of fungal infections either superficial or systemic has been increasing. Moreover, fungal infections become more difficult to treat when they show coupling with immunogenic diseases like AIDS. Superficial fungal infections are associated with skin, nail and eye and are less prominent to systemic infection. However, it may be dangerous if not treated properly. It is usually observed that conventional formulations including cream, powder, gels etc. are used to treat skin fungal infections even for the deep seated fungal infections. However, these formulations show various side-effects on the application site like burning, redness and swelling. Further, due to the immediate release of drug from these formulations they can stimulate the immune system of body generating high impact allergic reactions. Deep seated fungal infections like invasive aspergillosis and invasive candidiasis may be more difficult to treat because the drug released from conventional topical formulation can not reach at the target site due to the low penetration capacity. Similarly, in case of fungal infection of nail and eye, conventional formulations show problem of less bioavailability. Thus, to overcome the drawbacks of conventional therapy a lot of research works have been carried out to develop novel formulations of antifungal drugs to deliver them superficially. Novel formulations explored for the skin delivery of antifungal drugs include liposomes, niosomes, ethosomes, microemulsions, nanoparticles, microspheres and micelles. These formulations show extended or sustained release of drug, minimizing the side effect on application site, enhancing bioavailability and reducing the dosing frequency. Further, these formulations also show penetration into the deep skin to treat invasive fungal infections. Novel formulations explored in treatment of fungal infections of eye are liposomes and nanoparticles and whether for nail fungal infections microemulsions are the choice. In present article, we have discussed about conventional treatment of superficial fungal infection and their comparison with the novel drug delivery systems.